Educational Transformation Through Holistic Literacy by Applying Digital Technology Innovation at SMPN 04 Cipayung Village – Bekasi - Rismawati Rismawati; Miftakul Huda; Daspar Daspar; Donny Maulana (Inaba of Community Services Journal, 2024)
Globalization era gives quite an impact wide in various aspect life, incl demands in implementation of education. One of challenge real the is that education should capably produce resource humans who have competence, therefore That Transformation education through literacy holistic capable create development, updates and adjustments paradigm educator with demands era educational human resources are superior, creative, and innovative, among others with apply innovation digital technology as means for expand range transformation education culture. Use of online platforms, social media, and applications education help connect public with information, inspire participation active, and open door for learning collaborative. The impact covers enhancement participation in discussion, training, and dissemination of information related environment and literacy. The purpose of devotion to the public is to apply the role of education through educational transformation through literacy holistic with apply innovation digital technology. Methods used are observation, interviews, training, and counseling. Transformation education through holistic literacy with apply innovation digital technology shows that ability 21st century that is needed in the world of education are skills and learning innovate, information media and skills technology.